PERSEPSI SISWA KELAS VIII DALAM MENINGKATKAN MOTIVASI BELAJAR MENGGUNAKAN KURIKULUM MERDEKA - Aini Sudirman, Nurul; Fadillah, Nurul; Cahya Bening, Vannesa; Mukhlis, Muhammad (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The reason researchers examined perceptions in increasing learning motivation was so that they could find out how perceptions influenced student learning motivation at SMPN 1 Tembilahan. The problem of this research is how the response from class VIII students about increasing learning motivation using the independent curriculum. Data collection from May 10 to June 10 2023, totaling 31 data. The method used in this research is descriptive qualitative method with survey method. The researcher used the survey method with the preparation of the researcher looking for data related to students' perceptions of learning using the independent curriculum, in the form of a theoretical companion book and making a questionnaire to distribute to class VIII students at SMPN 1 Tembilahan. This study aims to describe the learning motivation of class VIII students by using the Merdeka Curriculum in learning Indonesian. The results of this study prove that the learning motivation of class VIII students using the independent curriculum, the researcher found 31 respondents. Researchers found that many respondents chose to strongly agree with the Merdeka Curriculum in Indonesian language subjects